Hybrid Methods of Molecular Modeling - Tchougréeff, Andrei L. (Progress in Theoretical Chemistry and Physics, 2008)
Hybrid Methods of Molecular Modeling is a self-contained advanced review volume. It provides a step by step derivation of the consistent theoretical picture of hybrid modeling methods and a thorough analysis of the concepts and current practical methods of hybrid modeling based on this theory. The book presents its material sequentially, paying attention both to the physical soundness of the approximations used and to the mathematical rigor necessary for the practical development of the robust modeling code. Historical remarks are given when it is necessary to put the current work in a more general context and to establish a relationship with other areas of computational chemistry. The reader should have experience with the rudimentary concepts of computational chemistry and/or molecular modeling. A basic knowledge of operators, wave functions, and electron densities is required. The book is also intended both for practicing experts in computational materials science, nanoscience, biochemistry, and those who are interested in broadening their knowledge with the current concepts of hybrid modeling and its limitations.